Arka Ranjini: A novel Gladiolus cultivar - Rao, T Manjunatha; Negi, S S; Janakiram, T; Kumar, Rajiv; Bharathi, T Usha; Sujatha, S (Indian Horticulture, 2021)
Gladiolus, is commercially grown worldwide for its magnificent s pike with array of colourful florets and is called as Queen of bulbous flowers. There is a demand for new genotypes having novel attractive flower colour, improved spike qualities like spike with compactly arranged florets in double rows, more number of spikes per plant, more number of florets remain open at a time and good cor m multiplication ability. To meet this demand, during 2019, scientists at ICAR-IIHR, Bengaluru have identified for release one novel gladiolus cultivar i.e. Arka Ranjini for its quality florets and spike. It is suitable for cut flower, bouquet preparation, floral arrangement and garden display.